THE IMPACT OF OCCUPATIONAL SAFETY AND HEALTH (OSH) TRAINING ON FOSTERING A CULTURE OF SUSTAINABILITY IN THE WORKPLACE: A SYSTEMATIC LITERATURE REVIEW - Karim, Hazrul Hizam; Che Leh, Azmi; Chuen, Nurhan Norris Ma Weng; Buang, Nurul Fairuz; Abd Jalil, Nor Aslina; Azizan, Ahmad Salahuddin M (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2025)
This systematic literature review studies the impact of Occupational Safety and Health (OSH) training in developing a culture of sustainability in workplaces. It has become increasingly recognized that OSH training plays an important role for organizational sustainability and that safety procedures and practices must be part of any organisation's long-term future. However, there is relatively little literature that investigates the effectiveness of OSH training to establish sustainable behaviours and cultures at work. Therefore, in order to close this gap in research, PRISMA (Preferred Reporting Items for Systematic Reviews and Meta Analyses) guidelines were used to find and assess studies from sops and Web of Science (WoS) databases in a systematic way focusing on occupational risk factors, safety management systems, psychosocial factors, well-being of employees, and productivity outcomes. After searching, screening and assessing eligibility, there were 36 papers from the literature available that were peer reviewed and published between 2022 and 2024 that were assessed. The outcomes were divided into three themes: (1) Workplace Safety Management and Occupational Hazards, (2) Worker Training, Education, and Workplace Safety Interventions, and (3) Psychosocial Factors, Well-being, and Productivity. The results highlighted that OSH education strengthens employees' understandings of hazards and promotes sustainable safety behaviors, and leads to safety compliance, fewer incidents at work, and foster stronger psychological safety environments. Psychosocially based OSH training was positively related to employee's mental health, job satisfaction, and organizational commitment. Overall, there is clear evidence that systematically incorporating OSH training into workplace policies and culture can lead to more sustainable organizational outcomes. Future research should examine long-term effects and contextual elements that contribute to the effectiveness of OSH training across industry sectors.